Discovery of Raman-scattered lines in the massive luminous emission-line: Star LHA 115-S 18 - Torres, Andrea Fabiana (2012)
LHA 115-S 18 is a very peculiar emission-line star exhibiting the B[e] phenomenon. Located in the Small Magellanic Cloud, its spectrum shows features of an extremely wide range of excitation and ionization stages, extending from highly ionized atomic lines (Si IV, CIV, HeII) in the ultraviolet and optical regions to molecular emission bands of CO and TiO in the optical and infrared regions. The most distinguishing spectral characteristic of LHA 115-S 18 is the high variability detected in the He II λ4686 emission line, which can be a very conspicuous or completely invisible feature. In thiswork,we report on another peculiarity ofLHA115-S 18. From high-resolution optical spectra taken between 2000 and 2008, we discovered the appearance and strengthening of two emission features at λλ6825 and 7082Å, which we have identified as Raman-scattered lines. This is the first time that these lines have been detected in the spectrum of a massive luminous B[e] star. As the classification of LHA 115-S 18 is highly controversial, we discuss how the discovery of the appearance of Raman-scattered lines in this peculiar star might help us to solve this puzzle.